2019
DOI: 10.1590/1980-5373-mr-2018-0316
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anatase Nanoparticles on the Mechanical Properties and the Bacterial Adhesion to Acrylonitrile-Butadiene-Styrene Terpolymer

Abstract: This work aims to synthesize composite material which combines adequate mechanical properties and high resistance to bacterial adhesion. Such materials are needed in many components in the medical, industrial, and environmental applications. To obtain that combination, high weight percents of anatase nanoparticles, as bacterial adhesion reducer, were incorporated into a matrix of the ABS terpolymer. Pseudomonas aeruginosa, Staphylococcus aureus, and Klebsiella pneumonia were selected for the bacterial adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…They also revealed a lower complex viscosity above Tg would improve anisotropy by creating a stronger layer to layer bond and increased surface area contact between layers. Al-Hydary et al [22] proved that the addition of anatase nanoparticles into the ABS matrix improves the stiffness and the compressive strength of the terpolymer with a noticeable reduction in the flexural strength due to the development of minor defects in the structure. They also found that 10 wt % of anatase nanoparticles is suitable to obtain the best combination between the mechanical properties of composites and their high resistance to bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…They also revealed a lower complex viscosity above Tg would improve anisotropy by creating a stronger layer to layer bond and increased surface area contact between layers. Al-Hydary et al [22] proved that the addition of anatase nanoparticles into the ABS matrix improves the stiffness and the compressive strength of the terpolymer with a noticeable reduction in the flexural strength due to the development of minor defects in the structure. They also found that 10 wt % of anatase nanoparticles is suitable to obtain the best combination between the mechanical properties of composites and their high resistance to bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%